PENGARUH PERSEPSI SISWA TENTANG PEMBELAJARAN DARING MATA PELAJARAN IPS TERHADAP MOTIVASI BELAJAR PADA MASA PANDEMI COVID-19 DI SMP N 1 UNGARAN KELAS 8 TAHUN AJARAN 2020/2021 (Universitas Negeri Semarang, 2022)
During online learning cause of the COVID-19 pandemic, class VIII students at JHS 1 Ungaran during the implementation of online learning remain active in participating in learning, always submitting assignments on time, the environment around students supports the implementation of online learning, and social studies teachers can provide interesting learning for their students. The objectives of this study are (1) to describe students' perceptions of online learning in social studies subjects, and (2) to describe the effect of students' perceptions of online learning on learning motivation in social studies subjects. The research method used is ex-post facto research method. Sampling using simple random sampling technique. The data analysis technique of this research uses simple linear regression analysis. The results of the research conducted showed that there was a positive and significant effect on students' perceptions of online learning for social studies subjects on learning motivation in class VIII of Junior High School 1 Ungaran. Selama pembelajaran daring masa pandemi covid-19 siswa kelas VIII di SMP N 1 Ungaran selama pelaksanaan pembelajaran daring tetap aktif mengikuti pembelajaran, selalu mengumpulkan tugas dengan tepat waktu, lingkungan sekitar siswa mendukung pelaksanaan pembelajaran daring, serta guru IPS mampu memberikan pembelajaran yang menarik bagi siswanya. Tujuan penelitian ini adalah (1) menguraikan persepsi siswa tentang pembelajaran daring pada mata pelajaran IPS, dan (2) menguraikan pengaruh persepsi siswa tentang pembelajaran daring terhadap motivasi belajar pada mata pelajaran IPS. Metode penelitian yang digunakan adalah metode penelitian ex-post facto. Pengambilan sampel menggunakan teknik simple random sampling. Teknik analisis data penelitian ini menggunakan analisis regresi linear sederhana. Hasil dari penelitian yang dilakukan menunjukan bahwa ada pengaruh positif dan signifikan persepsi siswa tentang pembelajaran daring mata pelajaran IPS terhadap motivasi belajar di kelas VIII SMP Negeri 1 Ungaran.